Perceptions of Parents and Nurses on Needs of Hospitalized Children\'s Parents - R Karimi; Z Daneshvar; AS Sadat Hoseini; A Mehran; M Shiri (Tehran University of Medical Sciences, 2008)
Background & Aim: Due to the fact that family centered care have a crucial role in pediatric nursing, it seems compatibility of nurses;apos and parents;apos perception about parents;apos needs can lead to deliver higher quality care. The aim of this study was to compare parents;apos and nurses;apos perceptions about needs of hospitalized children;aposs parents. Methods & Materials: This is a cross-sectional survey. One hundred and fifty parents and 80 nurses were selected using convenient sampling method. Data was gathered using Kristjánsdóttir;aposs "parental needs of hospitalized children" questionnaire. Data were analyzed using descriptive and analytical (Chi-squared & Mann-Whitney U tests) methods. Results: Research findings showed that there was significant difference between both parents;apos and nurses;apos perceptions about parents;apos needs (P=0.012). Both groups believed that parents;apos needs are met partially in hospitals. There was not meaningful difference between the parents;apos and nurses;apos perceptions concerning meeting parental needs (P=0.666). Based on their perceptions, understanding of parents;apos needs help them to meet their requirements in health care facilities. There was a significant difference between parents;apos and nurses;apos perceptions regarding parents;apos need (P=0.018). Conclusion: Parents and nurses recognized all of the parents;apos needs to be important there were also deficits in meeting these needs. Therefore, parents;apos cooperation with health care team is necessary to facilitate the recovery of sick children as well as meeting parents;apos needs.